Lipid peroxidation activity in women with reproductive disorders and chronic endometritis - I. N. Danusevich; N. A. Kurashova; Y. G. Nadelyaeva; A. A. Geyn (Acta Biomedica Scientifica, 2016)
The research focuses on peculiarities of lipid peroxidation processes in women with reproductive disorders associated with chronic endometritis. The control group included 50 women of reproductive age with chronic endometritis, whose average age was 29.7 ± 4.7years. The comparison group consisted of 50 women of the same age with reproductive disorders without chronic endometritis, who had signed informed consent. We followed ethical principles and requirements of the Declaration of Helsinki of the World Medical Association. Insufficient activity of peroxidation processes which is characterized by a decrease in the concentration of primary ((DC - 1.11 ± 0.05 for the control group and 1.43 ± 0.08 for the comparison (p < 0.05)) peroxidation products, an increase in concentration of intermediate ((KD) - 0.53 ± 0.03 and 0.36 ± 0.03 respectively (r < 0,001)) peroxidation products and increased content of double bond substrates: 1.82 ± 0.07 and 1.11 ± 0.07 respectively (r < 0,001) compared to the patients with reproductive disorders without chronic inflammation of the endometrium which therefore indicates the presence of oxidative stress in women with reproductive disorders and chronic endometritis. The results of discriminant analysis showed that the diene conjugates are the most informative indicators of the lipid peroxidation system, indicating the differences between the group of patients with chronic endometritis and the group of patients without inflammation.